Interaksi Bahasa Dan Budaya Dalam Konteks Masyarakat Etnik: Studi Kasus Pada Kelompok Minoritas Di Indonesia - Tannia Alfianti Putri; Reisya Diva Maharani Putri; Taswirul Afkar (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
Indonesia is a country with extraordinary ethnic and cultural diversity, where each ethnic group has its own unique language and traditions. This research aims to explore the interaction between language and culture in the context of ethnic minority communities in Indonesia. The research method used is qualitative with a descriptive approach through literature analysis from previous research and field reports. The results show that ethnic languages play an important role in maintaining cultural identity and social cohesion among minority communities. Language is used in various cultural contexts, such as traditional rituals and religious ceremonies, as well as in everyday life to maintain cultural values. Challenges faced include the dominance of Indonesian and globalization, which reduces the use of ethnic languages among the younger generation. However, there are various revitalization efforts through education, social media and digital technology to preserve their language and culture. In conclusion, the interaction of language and culture in ethnic minority communities in Indonesia is a complex and dynamic phenomenon, requiring support from the government and educational institutions for sustainable preservation.